Clinical efficacy of myometrial and endometrial microwave ablation in the treatment of patients with adenomyosis who had anemia. (31st December 2022) - Li, Zuolin; Li, Xiaolian; Lin, Min; Qiu, Sihua; Wang, Liangqin; Lai, Liping; Luo, Xuefen; Mo, Zunyu; Dong, Gang; Lyu, Guorong; Li, Shuiping
Abstract: Objective: This study evaluated the clinical efficacy of myometrial and endometrial microwave ablation (MEWA) for treating adenomyosis in patients with anemia. Methods: This retrospective study enrolled 64 patients with adenomyosis who had anemia treated with either MEWA (MEWA group) or myometrial microwave ablation (MMWA group) between May 2019 and May 2021. The uterine volumes, uterine-volume reduction rates, hemoglobin (Hb) levels, cancer antigen 125 (CA125) levels, dysmenorrhea visual analog scale (VAS) scores, uterine fibroblast symptoms and health-related quality of life (UFS-QOL) scores, menstrual flow scores (MFS) before and 3, 6, and 12 months post-treatment, and adverse events and complications in both groups were collected to assess clinical efficacy. Results: No statistically significant preoperative differences were observed in any measured factors. Postoperatively, there was a significant reduction in uterine volume and CA125 level, an increase in Hb level, and improvement in the UFS-QOL, dysmenorrhea VAS score, and MFS. No differences were observed in postoperative uterine volume, CA125 level, overall response rate, and adverse event rate during the follow-up period until 12 months postoperatively. However, the MEWA group showed a better uterine-volume reduction rate 6 months postoperatively and improvement in Hb level, USF-QOL score, dysmenorrhea VAS score, and MFS postoperatively. Conclusion: MEWA and MMWA demonstrated high clinical efficacy in treating adenomyosis and anemia. However, MEWA is a more effective therapy that successfully improves anemia, resulting in improved quality of life.